Assessing The Role Of Islamic Financing And Regional Economic Growth In Reducing Income Inequality: Evidence From Indonesia - Nani Suhartini; Tenny Badina; Nurul Fadhilah; Windiya Saputri; Nurlatifah Umi Oktafiani (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2025)
This study aims to analyse the impact of Zakat, Infak, and Sadaqah (ZIS) distribution, Islamic financing, and Gross Regional Domestic Product (GRDP) on income inequality in Indonesia during the period 2019–2023. A quantitative approach was employed, utilising secondary data from the annual reports of BAZNAS, Islamic Banking Statistics published by the Financial Services Authority (OJK), as well as GRDP and Gini ratio data from The Global Economy. A panel data econometric model with the Fixed Effect Model (FEM) was applied to estimate the effects of the variables. The analysis included classical assumption tests to ensure model validity and coefficient estimation to capture the impact of each variable on the primary outcome. The distribution of ZIS funds had no significant effect on the Gini ratio (p-value: 0.8848), whereas Islamic financing (p-value: 0.0128) and GRDP (p-value: 0.0083) had a significant negative effect, indicating their contribution to reducing inequality. The model explained 96.01% of the variation in income inequality. Islamic financing and inclusive economic growth play a significant role in reducing income inequality, while optimisation of zakat management remains necessary. Strengthening access to Islamic financing, ensuring transparency in ZIS management, and fostering inclusive economic growth are essential to achieve sustainable social and economic justice.